THE VISUALITY OF MAINCHARACTER AND SUNDANESE HORROR VISUAL GRAMMER IN RIRIWA NU MAWA PATI, OPAT MADHAB SETAN AND KAWIN KA KUNTI COMICS - Kasmana NIM: 37014001, Kankan
Today, the Moslem Sundanese people live with modernity in various aspects. Yet,their belief in spirits that is derived from view of traditions and customs assimilated with Islamic religiousteachings, is still embedded in their minds. For the Sundanese people, spirits are an immaterial-spiritual phenomenon, not merely a narrative. Some of them even consider spirits as a reality. This view has influenced the quantity of popular media such as television, radio, including comics that raise this theme as its content.From 1979 to 1992, there were Sundanese comics containing material about spirits. These horror genre comics raised the socio-cultural theme of the Sundanese people regarding their belief in the spirits and the occult which was representedusing various aspects of Sundanese culture. Fromtwenty comics published at that time, three comics were selected. They were Ririwa nu Mawa Pati, Opat Madhab Setan and Kawin Ka Kunti. These three comics were chosen as they were considered to be very cultural and very close to the reality of the Sundanese people. This research evaluated the visuality of the main characters, which includes the visual aspects, roles, characterization, archetypes, and stereotype, as well as the visual grammar of the Sundanese horror in the selected comics. The embodiment of characters with all the attributes embedded in the main characters of the selected comics contains an in-depth aspects relating to the aspects of Sundanese culture. The grammar of these horror comics was presented in Sundanese style that it became distinctive and significant to be examined more deeply. In addition, this research is also supported by the fact that research on Sundanese comics with such topics and themes is still rare. This is a qualitative research and interdisciplinary approach is used to answer the research questions. Compositional interpretation analysis and intertextual analysis are used to examine the characters and also the visual grammar of the comic. This research is supported by theories about characters, archetypes and comics grammar which are then associated with the Sundanese context. As a 5 reference, an in-depth interview is done to obtain oral literature, customs and traditions concerning belief in spirits in Sundanese society. The results of this research will provide knowledge on the visualization of the main characters in the Sundanese comics. The categories and classifications of spirits known in the Sundanese society are more profound. This can be utilized as academic reference materials in the field of literature, culture, art and design, which can be applied to the practical world, such as roles, characterization, archetypes and stereotypes in the efforts of developing further cultural products. Similarly, the grammar of the selected Sundanese horror comics can be a practical reference in designing comics, especially Sundanese comics. The results can also be a reference to the religious system and beliefs of the Sundanese people, as one element of culture in the context of its influence on the variety of cultural products produced. Through this research, it is found that the visualization of the main characters is represented through the form, emotion, volume, coloring and lighting as well as diverse expression. These aspectsare related to the archetypes shown. In the main characters of the comics, there were more than one good archetype, namely the great mother, the heroes, the shadow, the self and the wise old man. Each character was told to have power that came from determination and a soul that wanted to change itself in order to be perfect.But visually, the characterswere portrayed as ambivalent with the power. It means that in this comic, the power stereotype was not always related to the physical character. The roles and archetypes of characters that appear were phase or process. In other words, the characterswere not perfect beings but they were in the process toward goodness, so they hadchanging roles and archetypes. The concept of the position of women in the Sundanese society was born in the chosen character. The role was equal to the male characters, complementary, became a binary opposition, and parental. The characters carried the values and views of the Sundanese people, i.e. babalik pikir (introspection & self improvement), do not disturb the property of others, do not be greedy, in order to be a perfecthuman (masagi). Through intertextual analysis, it is found that the main concept of the characters in the comic is an intertext form representing the reality of life (lifelikeness-the likeness of life), as a form of belief that influenced the view of Sundanese-Islamic cosmology. The three selected comics presented the grammar of horror through the aspects of content, such as the choice of moments, images, and words by bringing out the appearance of spirits with ruined form, abnormal, death objects, murder and sacrificial scenes. In these comics, the use of adjective word choices describingthe situations, feelings and senses which are related to the reality of the Sundanese people beliefs, were also dominant. Through the background elements, the Sundanese horror suggests a choice of time, place, social, natural phenomena, and weather that represent the nuance ofsilence and extreme fear in Sundanese style. This shows the proximity of the Sundanese people to the nature. In general, the three comics are categorized as the typical spiritual horror genre because these comics invite in-depth thinking, related to spirituality, religion and self-improvement before God